2019
DOI: 10.7717/peerj.7903
|View full text |Cite
|
Sign up to set email alerts
|

Oomycete metabarcoding reveals the presence of Lagenidium spp. in phytotelmata

Abstract: The oomycete genus Lagenidium, which includes the mosquito biocontrol agent L. giganteum, is composed of animal pathogens, yet is phylogenetically closely related to the well characterized plant pathogens Phytophthora and Pythium spp. These phylogenetic affinities were further supported by the identification of canonical oomycete effectors in the L. giganteum transcriptome. In this study, culture-independent, metabarcoding analyses aimed at detecting L. giganteum in bromeliad phytotelmata (a proven mosquito br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…An unannotated L. giganteum ARSEF 373 whole-genome assembly (accession number GCA_002286825.1 ) is available in the NCBI Genome database ( 4 ), but we found that both cox1 gene sequences in this assembly differ extensively (~92% identity) from cox1 sequences previously amplified from L. giganteum isolates ( 5 ). Furthermore, one was nearly identical (>99.9%) to a DNA sequence ( SPLM01000079.1 ) in the oomycete Pythium oligandrum , a close relative of Lagenidium ( 6 ), suggesting the presence of contaminating DNA sequences.…”
Section: Announcementmentioning
confidence: 75%
“…An unannotated L. giganteum ARSEF 373 whole-genome assembly (accession number GCA_002286825.1 ) is available in the NCBI Genome database ( 4 ), but we found that both cox1 gene sequences in this assembly differ extensively (~92% identity) from cox1 sequences previously amplified from L. giganteum isolates ( 5 ). Furthermore, one was nearly identical (>99.9%) to a DNA sequence ( SPLM01000079.1 ) in the oomycete Pythium oligandrum , a close relative of Lagenidium ( 6 ), suggesting the presence of contaminating DNA sequences.…”
Section: Announcementmentioning
confidence: 75%
“…Some of the earliest applications of DNA metabarcoding involved the analysis of vertebrate diets [189] and this method remains a powerful tool for understanding herbivory and predation (see [125,[190][191][192]). More recently, metabarcoding has been used to reconstruct plant-pollinator networks [146,147] and identify economically important taxa [155] or those relevant to human health [193,194].…”
Section: Looking Forwardmentioning
confidence: 99%
“…However, other genes coding cuticle-degrading enzymes have been found, such as GH5_27 or GH20; these are characteristic of entomopathogens and are not observed in plant pathogens (Quiroz Velasquez et al 2014;Olivera et al 2016). This dichotomy suggests that fungal and oomycete entomopathogens not only share morphology and pathological strategies, but also evolutionary histories and ecological relationships (Leoro-Garzon et al 2019;Shen et al 2019).…”
Section: Oomycotamentioning
confidence: 99%